2012
DOI: 10.1378/chest.11-3164
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Pediatric Sleep-Disordered Breathing

Abstract: Sleep-disordered breathing (SDB) is a frequent condition in children. In the last 2 decades, associations between SDB and behavioral, neurocognitive, cardiovascular, and metabolic morbidities have been extensively reported, and dose-dependent relationships with certain polysomnographic measures and even sleep-related questions have been suggested. [1][2][3][4][5][6] However, the eventual impact of SDB on impairments in the quality of life of a developing child 7,8 may be best understood in the context of a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 39 publications
(47 reference statements)
2
31
1
Order By: Relevance
“…It is possible that parents who are aware of a possible link between SDB and behavioral problems could provide biased estimates of either measure. However, prior research using community samples has suggested strong associations between parent-reported and objectively measured snoring [49] and shown that parents are generally unaware of an association between SDB and psychiatric outcomes [69]. Thus, the potential for such bias here is likely low.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that parents who are aware of a possible link between SDB and behavioral problems could provide biased estimates of either measure. However, prior research using community samples has suggested strong associations between parent-reported and objectively measured snoring [49] and shown that parents are generally unaware of an association between SDB and psychiatric outcomes [69]. Thus, the potential for such bias here is likely low.…”
Section: Discussionmentioning
confidence: 96%
“…During the morning, following NPSG assessment, children were asked to complete the cognitive tasks outlined above, and parents responded to standardized surveys concerning sleep habits and behavioral outcomes. Snoring status was reported by a parent as “never,” “rarely” (once per week), “occasionally” (twice per week), “frequently” (three times per week), and “almost always” (more than four times per week) as part of a validated and commonly used questionnaire [49]. Prior research examining parent-reported snoring status in relation to PSG analysis of snoring has demonstrated high sensitivity (0.66–0.94) and moderate to high specificity (0.20–0.73), depending on specific snoring cut-off values used for analyses [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…These HC children resided in Chicago and were recruited through community announcements and distribution of materials in the Well Child Clinic at the University of Chicago Medical Center. All children were considered healthy, did not have any identifiable risk factors for the development of OSA, did not suffer from any specific disorder, and did not snore based on their responses to a validated questionnaire [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Spruyt and Gozal [12] have proposed a set of questions to identify pediatric SDB. Unfortunately, there are no surveys that reliably predict the PSG findings, that is, clinical evaluation does not reliably detect OSA.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Clinical questions for a severity hierarchy for sleep-disordered breathing are as follows [12]: Clinical questions for a severity hierarchy for sleep-disordered breathing are as follows [12]:…”
Section: Optionmentioning
confidence: 99%